Bottom-trawl catch composition in a highly polluted coastal area reveals multifaceted native biodiversity and complex communities of fouling organisms on litter discharge. (March 2020) - Crocetta, Fabio; Riginella, Emilio; Lezzi, Marco; Tanduo, Valentina; Balestrieri, Liliana; Rizzo, Lucia
Abstract: Areas subjected to anthropogenic impacts are important to test the effect of stressors on local biota. We assessed with trawl net the composition and abundance of megafauna, litter, and litter-fouling communities in the soft bottoms of the National Interest Priority Site (NIPS) of Bagnoli-Coroglio (Gulf of Naples, Tyrrhenian Sea) at different depths. The megafauna accounted for 3444 specimens referred to 133 taxa (91 invertebrates and 42 fishes), for a biomass of ~102 kg and including species of wide ecological and commercial interest. Metrics of community structure yielded high values. The NIPS, hence, is characterized by a high biodiversity. Litter accounted for 3590 items, mostly in plastic and ranging between 10< × ≤20 cm, for a weight of ~260 kg, with values of 299.2 item/km 2 and 21.67 kg/km 2 . The putative origin of most items was land-based (83.6%), whereas sea-based litter accounted for 16.4%. More than 50% of the litter items found showed colonization by invertebrates and/or molluscan egg masses. Marine benthic litter, thus, locally constitutes a complex issue since litter items hosted complex communities of fouling organisms. Future remediation procedures should take the resident NIPS biota into account and not disrupt the environmental balance of the area. Highlights: Megafauna, litter, and fouling communities were assessed in the NIPS Bagnoli-Coroglio. The NIPS is characterized by a high biodiversity. Marine litter is a serious issue in the NIPS. Litter items hosted complex communities of fouling organisms. Future remediation procedures should not disrupt the NIPS environmental balance.